Oxygen-Based Nanocarriers to Modulate Tumor Hypoxia for Ameliorated Anti-Tumor Therapy: Fabrications, Properties, and Future Directions - Li, Xianqiang; Wu, Yue; Zhang, Rui; Bai, Wei; Ye, Tiantian; Wang, Shujun (Frontiers in Molecular Biosciences, 2021)
Over the past five years, oxygen-based nanocarriers (NCs) to boost anti-tumor therapy attracted tremendous attention from basic research and clinical practice. Indeed, tumor hypoxia, caused by elevated proliferative activity and dysfunctional vasculature, is directly responsible for the less effective or ineffective of many conventional therapeutic modalities. Undeniably, oxygen-generating NCs and oxygen-carrying NCs can increase oxygen concentration in the hypoxic area of tumors and have also been shown to have the ability to decrease the expression of drug efflux pumps (e.g. P-gp); to increase uptake by tumor cells; to facilitate the generation of cytotoxic reactive oxide species (ROS); and to evoke systematic anti-tumor immune responses. However, there are still many challenges and limitations that need to be further improved. In this review, we first discussed the mechanisms of tumor hypoxia and how it severely restrict the therapeutic efficacy of clinical treatments. Then an up-to-date account of recent progress in the fabrications of oxygen-generating NCs and oxygen carrying NCs are systematically introduced, and the improved physicochemical and surface properties of hypoxia alleviating NCs for increasing the targeting ability to hypoxic cells are also elaborated with special attention to the latest nano-technologies. Finally, the future directions of these NCs, especially towards clinical transformation, are proposed. Based on this comprehensive overview, we expect to provide some valued enlightenments and proposals in engineering more effective oxygen-based NCs in this promising field.